HOTS-Based Formative Assessment: The Key to Improving The Quality of Learning - Adzidzah, Nur; Yudiawan, Agus (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
This study aims to explain Higher Order Thinking Skills (HOTS)-based formative assessment in learning and reveal the principle of constructivism in comprehensively building students' high-level thinking skills. Literature studies are used as a research method. Relevant literature derived from books and articles in scientific e-journals was collected through documentation techniques. Furthermore, the data obtained was analyzed for content. The results show that HOTS-based formative assessment is the key to improving the quality of learning. This assessment trains students to think critically, analyze, and solve problems independently. In addition, teachers can also get more accurate feedback on student learning development so that they can provide appropriate interventions. The theory of constructivism provides a solid foundation for developing HOTS-based formative assessments. These assessments measure students' learning achievements but also encourage students to think critically, creatively, and independently. By consistently implementing HOTS-based formative assessments, it can create graduates with the competencies needed to face the challenges of the 21st century.